Boardwalk summer : a novel - Jaeger, Meredith (William Morrow, an imprint of HarperCollinsPublishers, 2018)
In 1940 Santa Cruz, the winner of Miss California makes a shocking decision that leaves her name in the headlines, years later in 2007 Santa Cruz, Marisol investigates her grandfather's secrets, including his connection to a beauty queen.